STRENGTH AND DEFORMABILITY OF SPECIFIC SEDIMENTARY AND OPHIOLITHIC ROCKS - Marinos, P. V; Tsiambaos, G. (Bulletin of the Geological Society of Greece, 2010)
The paper deals with the evaluation of strength and deformability of sedimentary rocks and ophiolites based on the processing of laboratory testing results. Characteristic values and their typical range for the parameters σci, Ei , as well as the Modulus Ratio (MR) are presented. These parameters are significant for the estimation of the strength and deformability of the rock mass since σci is basic component for the solution of Hoek-Brown failure criterion and Ei and MR are important components of the latest rock mass deformability expression (Hoek-Diedrichs, 2006). The recent site investigation and laboratory work undergone for the design of numerous tunnels in the Greek territory provided very good and sufficient data, derived from a specifically established database, for the estimation of strength and deformability of specific rocks. These rocks are sandstones and siltstones of flysch and molassic formations, as well as limestones and ophiolites.